Novel Compound Heterozygous Mutations in IL-7 Receptor α Gene in a 15-Month-Old Girl Presenting With Thrombocytopenia, Normal T Cell Count and Maternal Engraftment - Zangari, Paola; Cifaldi, Cristina; Di Cesare, Silvia; Di Matteo, Gigliola; Chiriaco, Maria; Amodio, Donato; Cotugno, Nicola; De Luca, Maia; Surace, Cecilia; Ladogana, Saverio; Gardini, Simone; Merli, Pietro; et al. (Frontiers in Immunology, 2019)
Patients with severe combined immunodeficiency (SCID) exhibit T lymphopenia and profound impairments in cellular and humoral immunity. IL-7 receptor α (IL-7Rα) deficiency is a rare form of SCID usually presenting in the first months of life with severe and opportunistic infections, failure to thrive and high risk of mortality unless treated. Here, we report an atypical and delayed onset of IL7Rα-SCID in a 15-month old girl presenting with thrombocytopenia. Immunological investigations showed a normal lymphocytes count with isolated CD4-penia, absence of naïve T cells, marked hypergammaglobulinemia and maternal T cell engraftment. Targeted next generation sequencing (NGS) revealed two novel compound heterozygous mutations in IL-7Rα gene: c.160T>C (p.S54P) and c.245G>T (p.C82F). The atypical onset and the unusual immunological phenotype expressed by our patient highlights the diagnostic challenge in the field of primary immunodeficiencies (PID) and in particular in SCID patients where prompt diagnosis and therapy greatly affects the survival.